Historical declines in parrotfish on Belizean coral reefs linked to shifts in reef exploitation following European colonization - Muraoka, Wendy T.; Cramer, Katie L.; O’Dea, Aaron; Zhao, Jian-xin; Leonard, Nicole D.; Norris, Richard D. (Frontiers in Ecology and Evolution, 2022)
Humans have utilized the Mesoamerican Reef (MAR) for millennia but the effects of prehistorical and historical fishing on this ecosystem remain understudied. To assess the long-term coupling of reef ecosystem and human dynamics in this region, we tracked trends in the structure and functioning of lagoonal reefs within the Belizean portion of the MAR using fish teeth fossils and sediment accumulation rates within reef sediment cores. We then paired this with a timeline of demographic and cultural changes in this region’s human populations. The ~1300-year timeline encompassed in the core record shows that declines in the relative abundance and accumulation rate of teeth from parrotfish, a key reef herbivore, occurred at all three reef sites and began between ~1500-1800 AD depending on site and metric of abundance. A causality analysis showed that parrotfish relative abundance had a positive causal effect on reef accretion rates, a proxy of coral growth, reconfirming the important role of these fish in reef ecosystem functioning. The timing of initial declines in parrotfish teeth occurred during a time of relatively low human population density in Belize. However, declines were synchronous with cultural and demographic upheaval resulting from European colonization of the New World. The more recent declines at these sites (~1800 AD) occurred in tandem with increased subsistence fishing on reefs by multiple immigrant groups, a pattern that was likely necessitated by the establishment of an import economy controlled by a small group of land-owning European elites. These long-term trends from the paleoecological record reveal that current parrotfish abundances in central Belize are well below their pre-European contact peaks and that increased fishing pressure on parrotfish post-contact has likely caused a decline in reef accretion rates; the origins of reef degradation in the Belizean portion of the MAR began hundreds of years before the onset of modern declines resulting from the combined effects of local human disturbances and climate change.